Perancangan dan Analisis Antena Mikrostrip dengan Metode Aperture Coupled Feed pada Frekuensi 800 MHz - Pambudhi, Hanief Tegar; Darjat, Darjat; Zahra, Ajub Ajulian (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Problems antenna of conductor materials is rahter complicated construction and size are ussually quite large, so for purpose such as a cellular system is considered less efficient. For this purpose requires a simple antenna, a thin, easy to manufacture, and can be connected with other circuits. Then came the idea to design a microstrip antenna that antennas. In this final project, the Aperture Coupled Feed antennas is designed at a frequency of 800 MHz and 900 MHz. The materials used as the antennas is two layers of epoxy PCB (FR4), with 1.5 mm thick material and the dielectric constant of 4.785593. The first layer of substrate is used as a patch of the antenna, while the second layer is used as a Coupled Aperture, and than the third layer is used as a Feed line, the Coupled Aperture is connected between the patch and Feed line. The process begins with the antennas design based on existing theories. The next step is to design and simulate the performance of the antennas using the software. The software that used for simulation and design is IE3D V12. And the last step is measurement of antennas performance based on the value the working frequency, the ratio of receive power, VSWR, and radiation patterns. The form of radiation pattern of microstrip Aperture coupled feed antenna is directional. Result of simulation of microstrip Aperture Coupled Feed at a frequency of 800 MHz: resonant frequency = 0.801 GHz, return loss = -24.92 dB, bandwidth = 0.286 %, VSWR = 1.12, impedance matching = 51.2694 + j 1.02575, total gain = 4.02147, HPBW = 82.5923, microstrip Aperture Coupled Feed at a frequency of 900 MHz: resonant frequency = 0.900 GHz, return loss = -21.0602 dB, bandwidth = 0.344 %, VSWR = 1.192, impedance matching = 53.6359 + j -18.5635, total gain = 4.45903, HPBW = 103.2656. And on the result obtained for Aperture Coupled Feed microstrip antenna at a frequency of 800 MHz: resonant frequency = 840 MHz, VSWR = 1.32, power receieve = 0,109 mW, HPBW = 68ᵒ and 72ᵒ, Aperture Coupled Feed microstrip antenna at a frequency of 900 MHz: resonant frequency = 920 MHz, VSWR = 1.28, power receieve = 0,042 mW, HPBW = 105ᵒ and 135ᵒ Keyword : substrate material, Aperture Coupled Feed, antenna parameter, the working frequency antenna